Impact of surgeon-defined capsular incision during radical prostatectomy on biochemical recurrence rates - Mandel, Philipp; Kriegmair, Maximilian (World journal of urology, 2016)
PurposeTo determine the impact of intraoperative surgeon-defined incision of the prostatic capsule (CapI) on cancer recurrence and to give an overview of the different definitions of CapI. CapI during radical prostatectomy (RP) occurs in a non-negligible number of patients; still, its impact on biochemical recurrence (BCR) remains controversial as definition of CapI differs in literature.MethodsWe analyzed the data of 3253 consecutive RP between 2009 and 2011. Occurrence and side of intraoperative CapI was documented by the surgeon. Factors influencing CapI were addressed using logistic regressions. The impact of CapI on BCR was analyzed using Cox regressions including traditional prognosticators.ResultsMedian follow-up was 36.2 months. Unilateral (bilateral) CapI occurred in 22.2 % (12.1 %) of patients. CapI was reported more often following open RP (p < 0.0001) and nerve-sparing procedure (p = 0.0004). Three-year BCR-free survival was 78.8, 79.9 and 82.1 % (p = 0.13) for patients with no, unilateral and bilateral CapI. In multivariate analysis, pT-stage (p < 0.0001), Gleason grade (p < 0.0005) and nodal status (p < 0.0005) were significantly associated with BCR. However, CapI had no independent impact on BCR (unilateral vs. no CapI, p = 0.55, bilateral vs. no CapI, p = 0.32).ConclusionsIntraoperative CapI occurs in a relevant number of RP and is more frequent during nerve-sparing procedure and open RP. However, there seems to be no impact of CapI and its extent on the incidence of early BCR.